Terrorism and social media: Global evidence - Simplice Asongu; Stella-Maris I. Orim; Rexon T. Nting (African Governance and Development Institute (AGDI), 2019)
The study assesses the relationship between terrorism and social media from a cross section of 148 countries with data for the year 2012. The empirical evidence is based on Ordinary Least Squares, Negative Binomial and Quantile regressions. The main finding is that there is a positive relationship between social media in terms of Facebook penetration and terrorism. The positive relationship is driven by below-median quantiles of terrorism. In other words, countries in which existing levels of terrorism are low are more significantly associated with a positive Facebook-terrorism nexus. The established positive relationship is confirmed from other externalities of terrorism: terrorism fatalities, terrorism incidents, terrorism injuries and terrorism-related property damages. The terrorism externalities are constituents of the composite dependent variable.
Keywords: D83; O30; D74; 330; Social Media; Terrorism